Anger in the Íslendingasögur - Manning, G (2021)
This thesis examines the presentation of anger in the Íslendingasögur and argues that the quality of a character’s emotional expression is contingent on their sociocultural identity. It focuses on the nexus between anger and various modalities of masculinity. The first chapter outlines the social constructivist approach that the thesis adopts, as well as medieval Christianity’s perspective on anger. Section I (comprising chapters two and three) argues that descriptions of involuntary psychosomatic indicia, facial expressions, and bodily movements connote, to varying degrees, angry experience. Section II (comprising chapters four and five) investigates the nexus between anger and masculinities. Chapter four argues that saga-society’s hegemonic masculine ideal condemns rash anger and shows how angry experience is associated with the destabilisation of a saga-man’s masculine status. Chapter five demonstrates that female characters can grow angry without being met with societal opprobrium. Moreover, it argues that their manipulation of anger allows them to destabilise hegemonic masculinity to some extent, and, in some cases, assume a masculine social position themselves. It suggests that this phenomenon accords with Jack Halberstam’s concept of ‘female masculinity’. By establishing that the gendered status of a character’s emotional comportment is contingent on their sex, chapters four and five refute Carol Clover’s ‘one-sex, one-gender’ model of saga-society gender. Section III (comprising chapters six, seven, eight, and nine) considers masculine characters who exhibit angry practices particular to their socio-cultural identities and thus adhere to uniquely tailored emotive scripts. Chapters six and seven argue that elderly men and berserkir, excluded from pursuit of the hegemonic masculine ideal, use anger to facilitate their agency and physical prowess, respectively. Chapter eight argues that sovereign figures, already assuming a self-evident hegemonic position, regularly wield anger as a means of establishing authority. Chapter nine argues that gods likewise wield anger, though often unsuccessfully, to maintain authority.